Externally Heated Valve Engine A New Approach to Piston Engines - Kazimierski, Zbyszko; Wojewoda, Jerzy (Springer Tracts in Mechanical Engineering, 2016)
This book reports on a novel approach for generating mechanical energy from different, external heat sources using the body of a typical piston engine with valves. By presenting simple yet effective numerical models, the authors show how this new approach, which combines existing internal combustion technology with a lubrication system, is able to offer an economic solution to the problem of mechanical energy generation in piston engines. Their results also show that a stable heat generation process can be guaranteed outside of the engine. The book offers a detailed report on physical and numerical models of 4-stroke and 2-stroke versions of the EHVE together with different models of heat exchange, valves and results of their simulations. It also delivers the test results of an engine prototype run in laboratory conditions. By presenting a novel theoretical framework and providing readers with extensive knowledge of both the advantages and challenges of the method, this book is expected to inspire academic researchers, advanced PhD students and professionals in their search for more effective solutions to the problem of renewable energy generation.